Biofiltration of Benzo[Alpha] Pyrene, Toluene and Formaldehyde in Air by a Consortium of Rhodococcus Erythropolis and Fusarium Solani: Effect of Inlet Loads, Gas Flow and Temperature - Diaz-Robles, L; Yanez-Sevilla, D (ELSEVIER SCIENCE SA, 2018)
Volatile organic compounds (VOCs) and polycyclic aromatic hydrocarbons (PAHs) are air contaminants with serious effects on human health. They include compounds with very different physicochemical properties, ranging from low to high volatility and low to high hydrophobicity. The objective of this research is to assess the feasibility of the simultaneous abatement of formaldehyde, a soluble and slightly polar VOC, toluene a hydrophobic and volatile VOC and benzo[alpha] pyrene (BaP), a representative PAH in a biofiltration reactor inoculated with the fungi Fusarium solani and the bacteria Rhodococcus erythropolis. Results obtained at an extended range of inlet loads: 3.7 to 447.7, 9.0 to 273.1 and 6.9 to 247.4 g m(-3) h(-1) of toluene, formaldehyde and BaP, respectively, show that the elimination capacity and removal efficiencies of the contaminants were largely independent of each other. Moreover, the system can accommodate a fivefold increase in inlet gas flow maintaining removal efficiencies close to 60% for all the contaminants tested when the inlet loads of contaminants were kept constant. The most dramatic decrease in elimination capacity and removal efficiency in the system was obtained by changing the temperature of the system, where a decrease from 25 degrees C to 17 degrees C reduced the formaldehyde removal efficiency from 67% to 43%. BaP and toluene removal efficiencies were less affected by the decrease in system s temperature. This study shows the high flexibility of a biofiltration system inoculated with F. solani and R. erythropolis for the abatement of toluene, formaldehyde and BaP.